Pengaruh Literasi Keuangan Dan Pendapatan Terhadap Pengelolaan Keuangan Generasi Z (Studi Kasus Pada Mahasiswa Universitas Komputer Indonesia yang Tercatat di INBISKOM Periode 2024-2025) - Ratna Komala, Adeh; Febriani Supriadi, Ayuni (JEMBA, 2025)
Good financial management is an important skill in supporting individual well-being and economic sustainability. In this context, Generation Z, as a group growing up in the digital era, has a strategic role and faces various challenges in managing finances wisely. This study aims to empirically test the influence of Financial Literacy and Income on the Financial Management of Generation Z, specifically students of the Indonesian Computer University registered with INBISKOM for the 2024-2025 period. The research method used is descriptive and verification analysis with a quantitative approach. The study population was UNIKOM students registered with INBISKOM, while the sampling technique used random sampling to obtain 126 respondents. Primary data was collected through questionnaires, then analyzed using multiple linear regression with the help of SPSS 27.0 for Windows software. The results show that financial literacy and income have a significant effect on the financial management of Generation Z.